Gene Profiles in Drug Design - Lidbury, Brett A;Ed. Mahalingam, Suresh;Ed (CRC Press/Taylor & Francis, 2009)
Explores the processes and technologies that yield gene profile-based drugs. This book focus on components or steps in the process of translating abstract gene profiles into tangible new drugs. It compares the advantages and pitfalls of various methods that have been used to generate gene profiles.